2020
DOI: 10.18632/aging.102760
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5-TRIM21 interaction regulates the senescence of osteosarcoma cells by targeting the TXNIP/p21 axis

Abstract: Osteosarcoma (OS) is the most common bone malignancy in adolescents and has poor clinical outcomes. Protein arginine methyltransferase 5 (PRMT5) has recently been shown to be aberrantly expressed in various cancers, yet its role in OS remains elusive. Here, we found that PRMT5 was overexpressed in OS and its overexpression predicted poor clinical outcomes. PRMT5 knockdown significantly triggered pronounced senescence in OS cells, as evidenced by the increase in senescence-associated β-galactosidase (SA-β-gal)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 59 publications
(89 reference statements)
1
19
0
Order By: Relevance
“…The U2-OS cells stably expressing H125-TRIM21 or H125-V were established previously and the MG63 stable cells were established using the same method 15 . U2-OS cells stably knocking down TRIM21 and its control cells were named as sh-TRIM21#1, sh-TRIM21#2, and sh-NC as previously described 16 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The U2-OS cells stably expressing H125-TRIM21 or H125-V were established previously and the MG63 stable cells were established using the same method 15 . U2-OS cells stably knocking down TRIM21 and its control cells were named as sh-TRIM21#1, sh-TRIM21#2, and sh-NC as previously described 16 .…”
Section: Methodsmentioning
confidence: 99%
“…For instance, TRIM21 has been demonstrated to be downregulated in hepatocellular carcinoma, breast cancer, and diffuse large B-cell lymphomas [10][11][12][13] , whereas other studies have shown that decreased expression of TRIM21 predicts better prognosis in pancreatic cancer patients 14 . We have recently demonstrated that TRIM21 plays a crucial role in regulating OS cell senescence and proliferation via interacting with several proteins, such as PRMT5 15,16 . However, it remains to be investigated whether TRIM21 plays a role in regulating OS autophagy and subsequent differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was shown that LCE1 (highly homologous to LCE2 and also encoded from the EDC locus) is a downstream target of p53 in cancer cell lines and inhibits the arginine methyltransferase, PRMT5, which is often upregulated in various cancers and a potential therapeutic target 65 . PRMT5 was also shown to have anti-senescence activity in osteosarcoma cells 66 . It remains to be elucidated whether or not LCE2, which was also p53-dependent in RIS cells ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TXNIP is a key factor in the DNA damage and cell aging induced by PRMT5 depletion. Targeting the PRMT5/TRIM21/TXNIP signal transduction pathway could provide new therapies for the treatment of OS (105).…”
Section: Txnip and Osteosarcomamentioning
confidence: 99%